The Importance of the Concept of Integration in the Process of Teaching Native Language - K., Ashurbayeva R. (Research Parks Publishers, 2023)
Today, in the reforms carried out in the education system of Uzbekistan, knowledge and skills are formed at the required level at each stage of continuous education, have their own worldview, and can express their opinion independently and freely in any speech situation. , is one of the main goals of training competitive personnel according to world standards. The realization of these goals places a great responsibility on mother tongue education in secondary general education schools. In this article, reflections on the effectiveness of the concept of quality organization of mother tongue education and the concept of integrated education and the principles of its implementation are reflected. It is also discussed that the criteria of integrative education are reflected in the activities of Eastern scientists.